Arsenic Transformation in Soil-Rice System Affected by Iron-Oxidizing Strain (Ochrobactrum sp.) and Related Soil Metabolomics Analysis - Qian, Ziyan; Wu, Chuan; Pan, Weisong; Xiong, Xiaoran; Xia, Libing; Li, Waichin (Frontiers in Microbiology, 2022)
Iron-oxidizing bacteria could oxidize Fe(Ⅱ) and mediate biomineralization, which provides the possibility for its potential application in arsenic (As) remediation. In the present study, a strain named Ochrobactrum EEELCW01 isolated previously, was inoculated into paddy soils to investigate the effect of iron-oxidizing bacteria (FeOB) inoculation on the As migration and transformation in paddy soils. The results showed that inoculation of Ochrobactrum sp. increased the proportion of As in iron-aluminum oxide binding fraction, which reduced the As bioavailability in paddy soils and effectively reduced the As accumulation in rice tissues. Moreover, the inoculation of iron oxidizing bacteria increased the abundance of KD4-96, Pedosphaeraceae and other bacteria in the soils, which could reduce the As toxicity in the soil through biotransformation. The abundance of metabolites such as carnosine, MG (0:0/14:0/0:0) and pantheine 4'-phosphate increased in rhizosphere soils inoculated with iron-oxidizing bacteria, which indicated that the defence ability of soil-microorganism-plant system against oxidative damage caused by As was enhanced. This study proved that iron-oxidizing bacteria have the potential application in remediation of As pollution in paddy soil and illustrated their regulatory mechanisms from the perspectives of microbial communities and metabolomics.